2023
DOI: 10.1177/08902070231156840
|View full text |Cite
|
Sign up to set email alerts
|

Examining individual differences in personality trait changes after negative life events

Abstract: Personality traits can change throughout the entire life span, but people differ in their personality trait changes. To better understand individual differences in personality changes, we examined personal (personality functioning), environmental (environmental changes), and event-related moderators (e.g., perceived event characteristics) of personality trait changes. Therefore, we used a sample of 1069 participants who experienced a negative life event in the last 5 weeks and assessed their personality traits… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 97 publications
(214 reference statements)
2
20
0
Order By: Relevance
“…A general theme in recent work on this topic involves the need to know more about the context surrounding life events. It should not be surprising to personality psychologists that people do not change in the same ways (Schwaba & Bleidorn, 2018) or that people may react differently to the same life event (Haehner et al, 2023), but individual differences in change have generally not been the focus of this area of research. Thus far, few reliable contextual moderators have been identified that help explain these different reactions.…”
Section: Discussionmentioning
confidence: 99%
“…A general theme in recent work on this topic involves the need to know more about the context surrounding life events. It should not be surprising to personality psychologists that people do not change in the same ways (Schwaba & Bleidorn, 2018) or that people may react differently to the same life event (Haehner et al, 2023), but individual differences in change have generally not been the focus of this area of research. Thus far, few reliable contextual moderators have been identified that help explain these different reactions.…”
Section: Discussionmentioning
confidence: 99%
“…But why do people differ in their changes in SWB after experiencing major life events? Answering this question is an ongoing challenge for research on major life events not only regarding the domain of SWB but also for research on event-related changes in personality traits and mental health (Bleidorn et al, 2020;Haehner, Bleidorn, & Hopwood, 2023;Luhmann et al, 2021). Some studies considered individual differences in personality traits, coping resources, or demographic characteristics to explain individual differences in the reaction to major life events (e.g., Anusic et al, 2014;Kuhn & Brulé, 2019;Mancini et al, 2011).…”
Section: Subjective Well-being and Major Life Eventsmentioning
confidence: 99%
“…Compared to these occurrence-based approaches to assess major life events, assessing event characteristics provides a more detailed understanding of the experienced event. Thus, considering event characteristics could help to address the question why people react differently to major life events (Haehner, Bleidorn, & Hopwood, 2023;Luhmann et al, 2021).…”
Section: Event Characteristics and Changes In Subjective Well-beingmentioning
confidence: 99%
See 2 more Smart Citations